2021
DOI: 10.3390/ma14020472
|View full text |Cite
|
Sign up to set email alerts
|

Assembling Surface Linker Chemistry with Minimization of Non-Specific Adsorption on Biosensor Materials

Abstract: The operation of biosensors requires surfaces that are both highly specific towards the target analyte and that are minimally subject to fouling by species present in a biological fluid. In this work, we further examined the thiosulfonate-based linker in order to construct robust and durable self-assembling monolayers (SAMs) onto hydroxylated surfaces such as silica. These SAMs are capable of the chemoselective immobilization of thiol-containing probes (for analytes) under aqueous conditions in a single, strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Earlier we had reported that a 4-cyanophenyl aminopropyltriethoxysilyl imine could be prepared and incorporated into a molecular rectifier so we wanted to use this method prepare a number of different imines from benzaldehydes with strong electron withdrawing groups (7) (Scheme 2) [2]. As expected, these reactions proceeded well to produce imines (8)(9)(10)(11) that can be isolated in high yield. As with all of these imines, they are best stored for long periods of time under nitrogen in a refrigerator.…”
Section: Imines Prepared From Cyano and Nitro Substituted Benzaldehydesmentioning
confidence: 69%
See 1 more Smart Citation
“…Earlier we had reported that a 4-cyanophenyl aminopropyltriethoxysilyl imine could be prepared and incorporated into a molecular rectifier so we wanted to use this method prepare a number of different imines from benzaldehydes with strong electron withdrawing groups (7) (Scheme 2) [2]. As expected, these reactions proceeded well to produce imines (8)(9)(10)(11) that can be isolated in high yield. As with all of these imines, they are best stored for long periods of time under nitrogen in a refrigerator.…”
Section: Imines Prepared From Cyano and Nitro Substituted Benzaldehydesmentioning
confidence: 69%
“…A series of small molecules containing aminopropyltriethoxysilane (APTES) linkers were synthesized so that they could potentially be incorporated into self-assembled monolayers (SAMS) on metal oxide surfaces. Trialkoxysilanes are widely used to modify metal oxide surfaces since they readily react with surface hydroxyl groups to release the alkanol and provide a piano stool trialkoxysilane linkage to the surface [1][2][3][4][5][6][7][8][9][10][11]. Two main structural aspects of the small molecules to be synthesized were considered: (1) ease of synthesis of the small molecule, i.e., where possible, one-pot reactions from inexpensive, commercially available starting materials, and (2) presentation of a variety of aromatic functional groups that would be of interest to others working to use SAMS as components of materials for molecular electronics or sensing applications.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] On a larger scale, the presence of pathogens on surfaces within clinical settings often leads to hospitalacquired infections with poor prognoses and high treatment costs. [4] Surface modifications aiming to prevent unwanted biological adhesion have been explored extensively. [5][6][7] In the context of reducing pathogen-related fouling, antibiotic coatings, [8][9][10] nanoparticlebased nanocomposite films, [11,12] and biosurfactant impregnation [13,14] have all been shown to provide varying degrees of suppression of bacterial adhesion.…”
Section: Transparent and Highly Flexible Hierarchically Structured Po...mentioning
confidence: 99%
“…[ 1–3 ] On a larger scale, the presence of pathogens on surfaces within clinical settings often leads to hospital‐acquired infections with poor prognoses and high treatment costs. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…Streptavidin specifically binds to these SAMs adopting a well-defined orientation. [43] It should be noted that biotin is also chiral, thus the SAMs will also be chiral. In addition to studying specifically and nonspecifically bound streptavidin, we have also made measurements from complexes formed by them and an antibody.…”
Section: The Chiral Layersmentioning
confidence: 99%